Is the family pet a risk for multidrug resistant infections? : thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Palmerston North, New Zealand - Toombs-Ruane, Leah (Massey University, 2019)
Risk factors for community-acquired urinary tract infections (UTI) caused by extended-spectrum beta-lactamase-(ESBL) and AmpC beta-lactamase-(ACBL) producing Enterobacteriaceae were investigated in a prospective case-control study conducted between August 2015 and September 2017. Both cases and controls were from the Auckland and Northland regions of New Zealand. A telephone questionnaire was delivered to participants, and the results analysed for putative risk factors for human infections. Analysis was performed using regression models, including factors around pet ownership and any other animal contact. Faecal samples were submitted from some households; this included samples from both people and companion animals. Isolates collected from index case urine samples and ESBL- or ACBL-producing faecal samples were sequenced and subsequently analysed through a bioinformatics pipeline. Pet ownership was not found to be a risk for human ESBL- or AmpC-producing infections in this study. Another important finding of this research was that E. coli ST-131 was the most commonly found bacteria associated with the UTI from people recruited into the case-control study. The strains of this sequence type were likely to have entered New Zealand in multiple introductions over the last 20 years. Transmission of ESBL-/ACBLproducing E. coli was also suspected to have occurred within households where a person had been recently infected with the same bacteria (in the form of a UTI) caused by an ESBL-/ACBL-producing Enterobacteriaceae. The results of this study as a whole indicate that while pets may not be a major risk for acquisition of ESBL/ACBL-producing bacteria, they are likely to play a role in the transmission of bacteria within homes and the community, and therefore warrant attention in future work.
Copyright is owned by the Author of the thesis. Permission is given for a copy to be downloaded by an individual for the purpose of research and private study only. The thesis may not be reproduced elsewhere without the permission of the Author.
Keywords: Escherichia coli infections; Transmission; Urinary tract infections; Risk factors; Pets; Social aspects; New Zealand; Drug resistance in microorganisms; Enterobacteriaceae